Systemic Cytokine and Chemokine Profiles in Individuals With Schistosoma mansoni Infection and Low Parasite Burden - Castro, Vanessa N.; Rodrigues, Jailza L.; Cardoso, Diogo T.; Resende, Samira D.; Magalhães, Fernanda C.; Souza, Dayane C.; Requeijo, Maira H.; Negrão-Corrêa, Deborah; Geiger, Stefan M. (Frontiers in Immunology, 2018)
Intestinal schistosomiasis, caused by the parasitic trematode Schistosoma mansoni, is a chronic disease and the prolonged and continuous exposure to S. mansoni antigens results in a deviation of the host’s immune response. For diagnosis, the Kato-Katz (KK) method is recommended, however, this method showed low accuracy in areas of low endemicity. This study aimed to characterize the cytokine and chemokine profile of individuals with an extremely low parasite load (less than 4 eggs per gram of feces), e.g. individuals who were detected by alternative parasitological methods, such as the saline gradient and/or Helmintex®. In order to search for immunological markers for infection, the immunological profile in serum samples of these individuals was then compared with patients detected with the KK method and with a higher parasite load and with individuals repetitively negative by extensive stool exams. The study was conducted in Northern Minas Gerais in a rural area of the Municipality of Januária. Serum samples of a total of 139 parasitologically well-characterized individuals were assessed for the following immunological markers by commercially available immunoassays: TNF-α, IL-1β, IL-6, IL-17A, IL-5, IL-10, IL-13, IL-33, IL-27, CCL3, CCL5, CXCL10, CCL11, and CCL17. As a result, there were no significant differences in concentrations or frequencies for immunological markers between egg-negative individuals or individuals with ultra-low ( 4 epg) or low (4-99 epg) parasite loads. However, we found significant correlations between egg counts and eosinophil counts and between egg counts and IL-1β or TNF-α concentrations., IL-1β or TNF-α concentrations. The most striking alterations were found in individuals with the highest parasite load ( 100 epg). They had significantly higher TNF-α concentrations in serum when compared with individuals with a low parasite load (4-99 epg) and CCL17 concentrations were significantly elevated when compared with egg-negative individuals. Radar diagrams of frequencies for cytokine and chemokine responders in each infection group confirmed a distinct profile only in the infection group with highest parasite loads ( 100 epg).